LEKSIKON ETHNO-FISHERY DALAM KEARIFAN LOKAL SUKU BUGIS DI TARAKAN, KALIMANTAN TIMUR (Sebuah Kajian Etnolinguistik) - Dwi Cahyono Aji (Adabiyyāt: Jurnal Bahasa dan Sastra, 2010)
Language reflects human conceptualization and interpretation of the world. A speaker’s perception of the world is organized or constrained by the linguistic categories his or her language offers, that language structure determines thought, how one experience and hence how one views the world. This paper describes lexicons of ethno-fishery and local wisdom of Bugis language in terms of the speaker’s conceptualization or interpretation of ethno-fishery. The research located in Tarakan, East Kalimantan by selecting farmer community of Bugis people. Spradley concept is used to determine informant. The principle requires that an informant must understand the culture. The interview of informants was performed by using snowballing technique. The data, mostly, are utterances and dialogues and are taken with a camera-phone and also note-taking techniques. The data, then, are verified and classified in its smaller forms, i.e. lexicon. Then, the lexicon was interpreted base on the cultural understanding sense. The result shows that the Bugis language has many lexicons of the water, soil, plant, and shrimp in Bugis cultural category.